Hackers: The Spirit of a Techno-Episteme - Grigenti, Fabio (Scenari, 2023)
The following text is intended to provide an initial philosophical interpretation of the so-called hacker culture. A brief historical and conceptual survey of the phenomenon in question will provided, starting with a problematisation of the expression ‘to hack’. It will conclude by highlighting some elements of analysis that lead to interpret hacker practice as a form of techno-episteme.